Exploring the Catalytic Promiscuity of Phenolic Acid Decarboxylases: Asymmetric, 1, 6‐Conjugate Addition of Nucleophiles Across 4‐Hydroxystyrene. Issue 12 (8th May 2017) - Payer, Stefan E.; Sheng, Xiang; Pollak, Hannah; Wuensch, Christiane; Steinkellner, Georg; Himo, Fahmi; Glueck, Silvia M.; Faber, Kurt
Abstract: The catalytic promiscuity of a ferulic acid decarboxylase from Enterobacter sp. (FDC_ E s) and phenolic acid decarboxylases (PADs) for the asymmetric conjugate addition of water across the C=C bond of hydroxystyrenes was extended to the N‐, C‐ and S‐nucleophiles methoxyamine, cyanide and propanethiol to furnish the corresponding addition products in up to 91% ee . The products obtained from the biotransformation employing the most suitable enzyme/nucleophile pairs were isolated and characterized after optimizing the reaction conditions. Finally, a mechanistic rationale supported by quantum mechanical calculations for the highly ( S )‐selective addition of cyanide is proposed. Abstract :